2013
DOI: 10.1111/papr.12126
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wait times on Spinal Cord Stimulation Therapy Outcomes

Abstract: To improve SCS success rates, physicians involved in the treatment for chronic pain should refer these cases early to an implant physician once failure of medical management becomes apparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 29 publications
(81 reference statements)
4
40
2
4
Order By: Relevance
“…If the average wait time for SCS implantation is roughly five‐years, as reported from their single‐institution study, this certainly decreases long‐term success rates. Interestingly, they also noted that non‐implanting neurosurgeons referred to an implant physician around 1.7 times earlier than orthopedic surgeons and anesthesiologists , highlighting provider practice variability. Our results do not delineate provider types (orthopedic surgery, neurosurgery, pain management, and PM&R) within volume groups or procedure setting (acute care centers, private hospitals, or large academic centers); however, differences undoubtedly exist across different providers based on training, standard practice, and institutional variability.…”
Section: Discussionmentioning
confidence: 99%
“…If the average wait time for SCS implantation is roughly five‐years, as reported from their single‐institution study, this certainly decreases long‐term success rates. Interestingly, they also noted that non‐implanting neurosurgeons referred to an implant physician around 1.7 times earlier than orthopedic surgeons and anesthesiologists , highlighting provider practice variability. Our results do not delineate provider types (orthopedic surgery, neurosurgery, pain management, and PM&R) within volume groups or procedure setting (acute care centers, private hospitals, or large academic centers); however, differences undoubtedly exist across different providers based on training, standard practice, and institutional variability.…”
Section: Discussionmentioning
confidence: 99%
“…Это, в свою очередь, приводит к большой длительности периода между появлением болевого синдрома и имплантацией сис-темы спинальной нейростимуляции. Например, для па-циентов K. Kumar и соавторов [76] в Канаде это время составляло в среднем более 5 лет. При этом доля па-циентов, у которых SCS имела достоверный позитив-ный эффект, обратно пропорциональна этому сроку и составляла более 80% у пациентов со сроком до имп-лантации SCS менее 2 лет, 40-50% при сроке 5-8 лет и около 10% при сроке более 10 лет [76].…”
Section: Reviewsunclassified
“…Например, для па-циентов K. Kumar и соавторов [76] в Канаде это время составляло в среднем более 5 лет. При этом доля па-циентов, у которых SCS имела достоверный позитив-ный эффект, обратно пропорциональна этому сроку и составляла более 80% у пациентов со сроком до имп-лантации SCS менее 2 лет, 40-50% при сроке 5-8 лет и около 10% при сроке более 10 лет [76]. Кроме того, SCS имеет высокую эффективность только у части па-циентов, а рандомизация приводит к формированию смешанных в этом отношении групп.…”
Section: Reviewsunclassified
“…Kumar et al observed an inverse correlation between the long-term success rate and the time interval between the onset of the chronic pain syndrome and SCS implantation. They noted that the success rate in patients who received their SCS system within the first 2 years of their pain syndrome was 85%, whereas the success rate was 9% in patients with a more than 15-year history of chronic pain 126,127. As a consequence, an SCS trial should be performed within the first 2 years after onset of pain.…”
Section: Long-term Outcomes and Place In Therapymentioning
confidence: 99%